Widths and entropy numbers of the classes of periodic functions of one and several variables in the space B_q,1 - Pozharska, K.V.; Romanyuk, A.S.; Romanyuk, V.S. (Carpathian Mathematical Publications, 2024)
Exact-order estimates are obtained for the entropy numbers and several types of widths (Kolmogorov, linear, trigonometric and orthowidth) for the Sobolev and Nikol'skii-Besov classes of one and several variables in the space B_q,1, 1 <q< ∞. It is shown, that in the multivariate case, in contrast to the univariate, the obtained estimates differ in order from the corresponding estimates in the space L_q.